Integration of Halaika Local Culture in Formal Education System: Efforts to Maintain Traditional Values in the Digitalization Era of the Boti Dalam Tribal Community - Yonly Adrianus Benufinit; Jhon Enstein; Femberianus Sunario Tanggur (JURNAL PENDIDIKAN IPS, 2024)
This research explores the integration of local culture “Halaika” into the formal education system of the Boti Dalam community amidst the challenges of education digitalization. The Boti Dalam community faces a dilemma between the importance of formal education to prepare the younger generation for the times and concerns about the negative impacts of technology. One of the main challenges faced is how to integrate Halaika cultural values that emphasize harmony with nature and avoidance of excessive use of technology into the formal education curriculum without compromising the quality of education. This research used a descriptive qualitative approach with data collection techniques through in-depth interviews, focus group discussions (FGDs) and participatory observation involving traditional leaders, parents, students and teachers. The results show that the Halaika teachings serve as a safeguard against the negative influence of the digitalization of education but also reveal challenges in integrating these traditional values into formal education. Although there is a growing awareness among the Boti Dalam community about the importance of local wisdom-based education, the main challenges faced are the lack of training for teachers as well as the limited resources available. Therefore, collaboration between educational institutions and the government, as well as the development of specialized training for teachers, is needed to create programs that support the integration of Halaika values.